Characterization and neurogenic responses of primary and immortalized Müller glia - Tran, Thi-Hang; Lukmanto, Donny; Chen, Mei; Strauß, Olaf; Yamashita, Toshiharu; Ohneda, Osamu; Fukuda, Shinichi (Frontiers in Cell and Developmental Biology, 2025)
Primary Müller glia (MG) have been reported to exhibit a neurogenic capacity induced by small molecules. However, whether immortalized mouse MG cell lines exhibit neurogenic capacities similar to those of primary mouse MG remains unclear. In this study, we examined the morphology, proliferation rate, and marker profile of primary MG cells isolated from postnatal mouse pups with two immortalized mouse MG cell lines, QMMuC-1 and ImM10, in a standard growth medium. After chemical induction, we compared the morphology, markers, direct neuronal reprogramming efficiency, and axon length of these cell types in two culture media: Neurobasal and DMEM/F12. Our results showed that in standard growth medium, QMMuC-1 and ImM10 cells displayed similar morphology and marker profiles as primary MG cells, with the only differences observed in nestin expression. However, QMMuC-1 and ImM10 cells exhibited much higher proliferation rates than the primary MG cells. Following chemical treatment in both Neurobasal and DMEM/F12 media, a subset of primary MG, QMMuC-1, and ImM10 cells was induced to differentiate into immature neuron-like cells by day 7. While primary MG cells showed similar neuronal reprogramming efficiency and axon length extension in both media, QMMuC-1 and ImM10 cells displayed variations between the two culture media. Moreover, some of the induced neuronal cells derived from primary MG cells expressed HuC/D and Calbindin markers, whereas none of the cells derived from QMMuC-1 and ImM10 cells expressed these markers. Subsequent observations revealed that induced immature neuron-like cells derived from primary MG cells in both types of media and those derived from ImM10 cells cultured in DMEM/F12 survived until day 14. Taken together, our findings suggest that the two immortalized cell lines, QMMuC-1 and ImM10, exhibited neurogenic capacities similar to those of primary MG cells to some extent but did not fully recapitulate all their characteristics. Therefore, careful consideration should be given to culture conditions and the validation of key results when using immortalized cells as a substitute for primary MG cells.